A Novel Absorbent of Nano-Fe Loaded Biomass Char and Its Enhanced Adsorption Capacity for Phosphate in Water. (27th November 2013) - Zhou, Hongguang; Jiang, Zhenmao; Wei, Shiqiang
Abstract : A novel composite adsorbent of Fe loaded biomass char (Fe-BC) was fabricated to treat phosphorus in water. Fe-BC was prepared by a procedure including metal complex anion incorporation and precipitation with the pyrolysis char of corn straw as supporting material. The abundant porous structures of the as-prepared sample can be easily observed from its scanning electron microscopy (SEM) images. Observations by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses show that inorganic nanoiron oxides deposited in the composite could be amorphous hydrous iron oxide α -FeOOH. Adsorption of phosphate onto the Fe-BC composite and its precursor (BC) from aqueous solutions were investigated and discussed. The equilibrium adsorption data of phosphate was described by Langmuir and Freundlich models, and Langmuir isotherm was found to be better fitted than Freundlich isotherm. The maximum phosphate adsorption capacity for phosphate of Fe-BC was as high as 35.43 mg/g, approximately 2.3 times of BC at 25°C. The adsorption kinetics data were better fitted by pseudo-second-order model and intraparticle diffusion model, indicating that the adsorption process was complex. The Fe-BC composite has been proved as an effective adsorbent of phosphate from aqueous solutions owing to its unique porous structures and the greater Lewis basicity of the α -FeOOH.